Evaluasi Sistem Informasi Penjualan pada PT. Techpac Indo Informatika - Sari, Ratna (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Technological development is one effort that was relied upon by the company for the implementation of the company's activities. Technological developments have led to changes in data processing by the company from a manual system to a mechanical, electromechanical, and then to electronic or computerized systems. PT. Techpac Indo Informatika is a company that engaged in software distribution. The purpose of this research is conducting an evaluation and control through sales information system, especially input and output control, tosupport and provide the accurate and real-time information in decision making for top management The methodology used in this study is descriptive research method with data collection techniques using literature study by studying scientific books and various literature that related with this paper, field study that consists of interviews, observation and system testing. The results of evaluation and control for sales application system are expected to improve the weaknesses and present the accuracy and real-time data that reliable and trustworthy.